2017
DOI: 10.1177/0193945917692305
|View full text |Cite
|
Sign up to set email alerts
|

Acculturation and Physical Activity Among Latinas Enrolled in a 12-Month Walking Intervention

Abstract: This report evaluates the relationship between acculturation and assimilation with the physical activity outcomes of a 12-month walking intervention for postpartum Latinas (n=81, M age =29.2, M BMI = 30.0). Physical activity was measured by ActiGraph GT1M accelerometers. Acculturation and assimilation were measured by the Hazuda Acculturation and Assimilation Scales. Data were collected at baseline, 6-months, and 12-months. Results showed a trend for participants classified in the least acculturated groups to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 28 publications
0
9
1
Order By: Relevance
“…Current study participants had low acculturation levels and low levels of PA, which was consistent with the literature (Abraido-Lanza et al, 2017; Chang et al, 2018). Previous researchers who examined concepts of acculturation and assimilation found Latino females with low levels of acculturation engaged in more moderate-to-vigorous PA (Joseph, Benitez, Ainsworth, Todd, & Keller, 2018), contrasting with the current study. Dellasera et al (2018) found that Anglo acculturation was positively associated with PA in participants.…”
Section: Discussioncontrasting
confidence: 99%
“…Current study participants had low acculturation levels and low levels of PA, which was consistent with the literature (Abraido-Lanza et al, 2017; Chang et al, 2018). Previous researchers who examined concepts of acculturation and assimilation found Latino females with low levels of acculturation engaged in more moderate-to-vigorous PA (Joseph, Benitez, Ainsworth, Todd, & Keller, 2018), contrasting with the current study. Dellasera et al (2018) found that Anglo acculturation was positively associated with PA in participants.…”
Section: Discussioncontrasting
confidence: 99%
“…The role of acculturation might be a fruitful line of inquiry with regard to grandparents’ support for grandchildrens’ LTPA. Studies found acculturation level was negatively associated with physical activity among Latino Americans (Joseph, Benitez, Ainsworth, Todd & Keller, 2017; Singh, Yu, Siahpush, & Kogan, 2008; Unger et al, 2004). Latino grandparents’ positive attitude toward physical activity may be related to their active lifestyle in their native countries, where physical activity may have been a more salient and pervasive expectation (Sussner, Lindsay, Greaney, & Peterson, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…At the interpersonal level of influence, having a parent/guardian born in Mexico was found to protect against decreases in children’s GLTEQ score. Research suggests Hispanic mothers with high acculturation levels have lower physical activity than mothers with low acculturation [ 31 ]. Nativity is often used as a proxy measure for acculturation, but its validity is disputed partly for conflating lived experiences and effects inherited from the previous generation [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research suggests Hispanic mothers with high acculturation levels have lower physical activity than mothers with low acculturation [ 31 ]. Nativity is often used as a proxy measure for acculturation, but its validity is disputed partly for conflating lived experiences and effects inherited from the previous generation [ 31 ]. Our findings here suggest that children’s physical activity may be influenced in part by their parent’s nativity, supporting the claim that the experiences of one generation may reflect in the health outcomes of the following generation [ 32 ].…”
Section: Discussionmentioning
confidence: 99%